2014
DOI: 10.1155/2014/461941
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Flow Cytometry to Characterize Bacterial Physiological Responses

Abstract: Although reports of flow cytometry (FCM) applied to bacterial analysis are increasing, studies of FCM related to human cells still vastly outnumber other reports. However, current advances in FCM combined with a new generation of cellular reporter probes have made this technique suitable for analyzing physiological responses in bacteria. We review how FCM has been applied to characterize distinct physiological conditions in bacteria including responses to antibiotics and other cytotoxic chemicals and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
100
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 128 publications
3
100
0
1
Order By: Relevance
“…However the role of spontaneous lesions, including deaminated and oxidized bases in modulating this process in B. subtilis is currently unknown. Results have demonstrated that in a bacterial culture there is cell heterogeneity [6,16], and that the batch methods employed for physiologic characterization are limited, since the contribution of small populations could be overlooked [2,9]. Since mutation rates are low, even in the stressful starving conditions of stationary phase, a method of single-cell analysis such as Flow Cytometry (FCM) may be better suited for measuring mutations with the appropriate reporter system.…”
Section: Introductionmentioning
confidence: 99%
“…However the role of spontaneous lesions, including deaminated and oxidized bases in modulating this process in B. subtilis is currently unknown. Results have demonstrated that in a bacterial culture there is cell heterogeneity [6,16], and that the batch methods employed for physiologic characterization are limited, since the contribution of small populations could be overlooked [2,9]. Since mutation rates are low, even in the stressful starving conditions of stationary phase, a method of single-cell analysis such as Flow Cytometry (FCM) may be better suited for measuring mutations with the appropriate reporter system.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can be applied only in cases where the spores are still able to germinate. On the other hand, flow cytometry is a useful, rapid and high (20). Flow cytometry has been employed for many years as a method for single cell analysis and separation of eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometry has been employed for many years as a method for single cell analysis and separation of eukaryotic cells. However, so far it has remained challenging to distinguish among bacterial species or small size particles (20,21). Hence, studies reporting on flow cytometry as a tool for discriminating vegetative cells from spores of Bacillus subtilis remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Many different modalities have been established to quantify bacteria in planktonic and biofilm cultures, including direct cell enumeration (plate counting, microscopy, Coulter counting, and flow cytometry) [15][16][17][18][19][20][21][22][23][24][25], optical density [26][27][28], dry mass analysis [29][30][31], protein assays [32][33][34][35][36][37][38], and several staining methods [16,22,23]. The current gold standard method to quantify bacteria is cell enumeration by plate counting, offering multiple advantages.…”
Section: Introductionmentioning
confidence: 99%